Financial performance and generic strategy of Mexican stock enterprises before and during the Covid-19 pandemic - Roque López, Víctor Manuel (Advances in business related scientific research journal, 2025)
In the context of the COVID-19 period, this article aims to identify whether the type of strategy used by organisations (cost-based strategy and differentiation strategy) showed significant differences in financial performance indicators: net margin (NM), return on assets before taxes (ROA), and return on equity (ROE). Statistical analysis was performed using a multivariate technique considering non-metric independent variables (type of strategy) and metric dependent variables (financial indicators). The sample used considered companies listed on the Mexican Stock Exchange during the pre-COVID (2019), COVID (2020) and post-COVID periods (2021). The results from statistical tests provide evidence about the differences in the average financial results comparing the groups of companies using a particular strategy for a particular year, in the case of the Mexican companies analysed. The insights about a reaction to face a crisis derived from a pandemic are valuable for researchers, policymakers, and practitioners
Keywords: cost strategy; COVID19; differentiation strategy; financial performance; Hotelling’s T-square